Sex Differences in the Relation Between Supervision and Injury Risk Across Motor Development Stages: Transitioning From Infancy Into Toddlerhood. (21st February 2022) - Morrongiello, Barbara A; Corbett, Michael; Bryant, MA, Lindsay; Cox, MA, Amanda
Abstract: Rationale: Addressing a notable gap in research on injuries during infancy, this longitudinal study examined sex differences in the relationship between parents' typical levels of supervision and infants' injuries across motor development stages. Method: Parents were recruited and completed biweekly phone calls about their infant's motor skills. Once the infant was able to sit up independently, then a home visit was scheduled. Applying a participant-event monitoring method, parents were taught to complete diary forms (injury, supervision), which they started doing once the child could move from their seated location on the floor in some way (e.g., roll, crawl). Recordings continued until a month after the child could walk independently. Data (injury, supervision) were averaged within each motor development stage (low, high), and associations across stages were examined. Results: Model testing indicated that supervision level moderated the relation between injury rate across motor development stages, but the strength of this association varied by sex of the child. More intense supervision predicted lower injury rates for girls more so than for boys. Conclusions: Although the emergence of motor milestones has been associated with increased risk of injury during infancy, the current findings indicate that greater supervision can reduce this risk. However, supervision alone is not as effective to moderate injury risk for boys as it is for girls. Thus, for boys, additional strategies (e.g., hazard removal) may also be warranted to maximize reduction in their risk of injury as they acquire increasing motor skills.